Representation of Oneself and Others in a Transitional Society: Intergenerational Analysis - Demidov, A.A.; Ananyeva, K.I.; Samba, A.D.-B. (Èksperimentalʹnaâ psihologiâ, 2022)
The article examines the problem of the dynamics of psychological attitudes of the individual to himself and to other people in the context of the socio-cultural transformation of the living environment. The example of the Republic of Tuva shows the socio-cultural transformation for different age generations of Tuvans. The article presents the results of an empirical study of the attitude of Tuvans living in a remote area of ​​the Republic of Tuva, of different ages, towards themselves and other people - representatives of the Tuvan and Russian ethnos of different age generations. It is shown that, in the perceptions of Tuvan respondents of different age groups, there are "nuclear" qualities, characteristics, with the help of which representatives of their ethnic group are described in comparison with representatives of the Russian ethnic group. В статье рассматривается проблема динамики психологических отношений личности к себе и другим людям в условиях социокультурной трансформации жизненной среды. На примере Республики Тыва демонстрируется социокультурная трансформация для разных возрастных поколений тувинцев. Представлены результаты эмпирического исследования отношения тувинцев, проживающих в отдаленном районе Республики Тыва, разных возрастов к самим себе и другим людям - представителям тувинского и русского этноса разных возрастных поколений. Показано, что в представлениях тувинских респондентов разных возрастных групп существуют «ядерные» качества, характеристики, с помощью которых описываются представители своего этноса сравнительно с представителями русского этноса.